Organic fertilizer: Agro-industrial organic residue usage - Álvarez-Palomino, Laura; Vargas-Bayona, Javier Enrique; García-Díaz, Leidy K. (Spei Domus, 2018)
Theme and scope: agricultural activities worldwide produce a great amount of organic residue that doesn’t receive an adequate process and treatment for final disposal and cause contamination and degradation of the environment. An increasing strategy consist of its transformation in order to obtain new products, like organic fertilizers. Characteristics: a systematic review of the literature was carried out, including 150 publications between books, scientific articles and SciELO, Scopus, and ScienceDirect databases from 2000 to 2017. Fifty-five references were selected for analysis considering their usefulness and relevance in terms of usage and transformation of organic residue, reusable as organic fertilizer. Internal and external validity of the articles included were considered. Findings: it was found that fermentation processes like composting and bokashi result in sustainable alternatives for the elaboration of organic fertilizer from animal and vegetal agro-industrial residues. Its biggest impact relies on soil component, that receives macro and micro nutrients improving its physical, chemical and biological properties, along with the resul-ting soil, productivity and crop health improvement. Conclusions: it was found that composting and bokashi elaboration are the most frequent methods used for the production of organic fertilizers, with impact over agriculture, mainly because its actions in terms of the incorporation of organic matter to soils, the correction of nutritional needs, and the enhancement of its qualities for cultivation.